ATF4 Contributes to Ovulation via Regulating COX2/PGE2 Expression: A Potential Role of ATF4 in PCOS - Di, Fangfang; Liu, Jiansheng; Li, Shang; Yao, Guangxin; Hong, Yan; Chen, Zi-Jiang; Li, Weiping; Du, Yanzhi (Frontiers in Endocrinology, 2018)
Ovulatory disorder is common in patients with hyperprolactinemia or polycystic ovary syndrome (PCOS). Previous studies have shown that ATF4 plays critical role in apoptosis and glucose homeostasis, but its role in regulating reproductive function was not explored. The present study investigated the role of ATF4 in ovarian ovulatory function. Human granulosa cells (hGCs) from 48 women newly diagnosed with PCOS and 37 controls were used to determine ATF4 expression. In vitro cultured hGCs were used to detect the upstream and downstream genes of ATF4. A shRNA- Atf4 lentiviral vector (shAtf4) was injected into rat ovaries to establish an in vivo gene knockdown model to further assess the in vivo relevance of the results from PCOS women. We found that ATF4 expression was lower in hGCs from PCOS patients than in hGCs from non-PCOS women. Many pivotal transcripts involved in cumulus-oocyte complex (COC) expansion, extracellular matrix (ECM) remodeling, and progesterone production were significantly down-regulated after ATF4 knockdown. ChIP-qPCR assays indicated that ATF4 could directly bind to the COX2 promoter and that ATF4 knockdown could attenuate human chorionic gonadotropin (hCG)-induced COX2 expression and PGE2 production. The in vivo study showed that shRNA-lentivirus mediated Atf4 knockdown in rat ovaries led to reduced number of retrieved oocytes. Collectively, these findings suggested previously unknown roles of ATF4 in ovulation. Furthermore, ATF4 malfunction in PCOS patients may impact the ovulation process, which could contribute, in part, to the pathogenesis of PCOS.